Talking About Social Inequality: Three Concepts of Difference - Eva Barlösius (sozialpolitik.ch, 2023)
The article analyzes the categories and classifications of social inequality by asking which linguistic possibilities are available for developing concepts of social inequality. The article builds on Koselleck’s three kinds of differentiation: above and below, inner and outer, and earlier and later. It examines how these three kinds are used in the concepts of social inequality and demonstrates processes of shifting from one kind of differentiation to another.  In conclusion, I claim that the three kinds of differentiation reach their limits in increasingly heterogeneous societies that expect differences like sexual orientation and ethnicity to be equally valued and recognized.